Bildung in Germany and Its Implications for Chinese Adult Language Education - 蕊 华 (Adult Education Research Conference, 2023)
Examining and integrating the Bildung theories of Wilhelm von Humboldt and Lene Rachel Andersen, this paper suggests implications to overcome the current challenges in Chinese adult language education.
Keywords: Bilgung; Wilhelm von Humboldt; Lene Rachel Andersens; adult language education; implications